Basic statistics for the behavioral sciences - Heiman, Gary. (Belmont, USA : Wadsworth, 2014)
Offering a conceptual-intuitive approach, this popular book presents statistics within an understandable research context, deals directly and positively with student weaknesses in mathematics, and introduces new terms and concepts in an integrated way.